Label‐free bacterial colony detection and viability assessment by continuous‐wave terahertz transmission imaging. Issue 8 (6th May 2018) - Yang, Xiang; Shi, Jia; Wang, Yuye; Yang, Ke; Zhao, Xiang; Wang, Guiyu; Xu, Degang; Wang, Yunxia; Yao, Jianquan; Fu, Weiling
Abstract : Timely and accurate bacterial detection is critical for various health and safety applications, which promotes the continuous development of versatile optical sensors for bacterial investigations. Here, we report a new strategy for bacterial colony sensing using terahertz (THz) imaging with minimal assay procedures. The proposed method utilizes the acute sensitivity of THz wave to the changes in the water content and cellular structures. Single bacterial colonies of 4 bacterial species were directly distinguished using THz imaging by utilizing their differences in THz absorption. In addition, the distribution of mixed bacterial samples has been demonstrated by THz imaging, which demonstrated that the target bacterium could be easily recognized. Furthermore, we investigated the differentiation of bacterial viability, which indicated that bacteria under different living states could be distinguished by THz imaging because of their different hydration levels and cellular structures. Our results suggest that THz imaging has the potential to be used for mixed bacterial sample detection and bacterial viability assessment in a label‐free and nondestructive manner. Abstract : In this study, we used terahertz (THz) imaging to investigate the characteristics and distributions of different bacterial colonies and mixed bacterial samples. Single bacterial colonies of 4 bacterial species were directly distinguished as a result of their different THz absorption. In addition, same bacteria in different living states were successfully distinguished based on their different hydration levels and structural characteristics, demonstrating the potential of THz imaging for the label‐free assessment of bacterial viability.